Ukraine : Ex-Post Evaluation of Exceptional Access Under the 2015 Extended Arrangement-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2020)
This paper focuses on Ukraine's Ex-Post Evaluation of Exceptional Access Under the 2015 Extended Arrangement. Sound fiscal and monetary policies since the 2014-2015 crisis have resulted in a sharp reduction in Ukraine's external and internal imbalances. Public debt was put on a downward path, inflation has declined, and international reserves have recovered. The new Stand-By Arrangement will provide an anchor for the authorities' efforts to address the impact of the crisis, while ensuring macroeconomic stability and safeguarding achievements to date. Together with support from the World Bank and the European Union, it will help address large financing needs. The program will focus on safeguarding medium-term fiscal sustainability, preserving central bank independence and the flexible exchange rate, and enhancing financial stability while recovering the costs from bank resolutions. The National Bank of Ukraine has skillfully managed monetary policy during a very challenging period. Central Bank independence should be preserved, and monetary and exchange rate policies should continue to provide a stable anchor in the context of the inflation-targeting regime, while allowing orderly exchange rate adjustment and preventing liquidity stress.